Translation and Validation of the Patient Activation Measure in Portuguese People with Type 2 Diabetes Mellitus - Laranjo, Liliana (2018)
INTRODUCTION: Management of diabetes mellitus is largely dependent on patients' active participation in care. The 'Patient Activation Measure 13' assesses patients' knowledge, skills, and confidence in self-care. We aimed to translate, culturally adapt, and validate the 'Patient Activation Measure 13' to Portuguese, in people with type 2 diabetes. MATERIAL AND METHODS: The translation and cultural adaptation occurred in six phases. A convenience sample of people with type 2 diabetes was recruited from the waiting rooms of a diabetes outpatient centre in Lisbon, between March and April 2014. The questionnaire was self-administered; medical records were reviewed to obtain glycated haemoglobin levels. Main statistical analyses were based on the Rasch rating scale model. RESULTS: The response rate for the final questionnaire was 76%. Rasch analysis was conducted on 193 respondents. Respondents had a mean age of 67.1 (SD 10.1) years, 42.7% were women, and the mean patient activation measure score (0 - 100) in the sample was 58.5 (SD 10.1). The sample was low to moderate in terms of activation: 40.4% were low in activation (levels 1 and 2), 49.7% were in level 3, and 9.8% were in level 4, the highest level of activation. All items had good fit and the response categories functioned well. Item reliability was 0.97 and person reliability was between 0.77 (real) and 0.83 (model). DISCUSSION: The 'Patient Activation Measure 13' was translated and culturally adapted to European Portuguese and validated in people with diabetes, showing good psychometric properties. Future research should aim at evaluating test-retest reliability of the Portuguese 'Patient Activation Measure 13', and exploring its ability to measure changes in activation over time. CONCLUSION: The 'Patient Activation Measure 13' is now available in European Portuguese and has good psychometric properties.